Influence of Kidney Environment Parameters on Antibiotic Efficacy Against Uropathogenic Escherichia coli - Aust, Anne-Christine; Weigel, Markus; Herrmann, Jan-Paul; Shevchuk, Olga; Robert Engel, Daniel; Dobrindt, Ulrich; Hain, Torsten; Wagenlehner, Florian; Justus Liebig University Giessen (My University, 2024)
Background and objective: Urinary tract infections (UTIs) are common infections affecting the urinary system, predominantly caused by bacterial pathogens, with Escherichia coli being the most frequent pathogen. Infections of the kidney (eg, pyelonephritis) are severe and challenging to treat, due to the specific tissue microenvironment. In this study, the influence of different parameters mimicking the kidney environment on the effectiveness of antibiotics prescribed for pyelonephritis on the growth of uropathogenic strains was analyzed. Methods: To investigate the influence of different factors mimicking the kidney environment, we tested the effect of different kidney-representative concentrations of sodium chloride and urea, and different pH values on the efficacy of ertapenem, levofloxacin, and ceftriaxone. The effectiveness was assessed by determining the minimal inhibitory concentrations (MICs) against various E. coli strains. Key findings and limitations: The study revealed that pH significantly influences the MIC values of levofloxacin. Acidification of the pH led to an increase of the MIC values, while an alkaline pH had the opposite effect. The influence of sodium chloride and urea concentrations was strain and antibiotic specific. Since three different antibiotics were tested in this study, further research with additional antibiotics is warranted. Conclusions and clinical implications: These results suggest that the physicochemical conditions within the kidney can substantially influence the success of antibiotic therapy for pyelonephritis. Therefore, it is crucial for clinicians to consider these factors when selecting and dosing antibiotics. Further research is needed to evaluate a broader range of antibiotics and additional environmental parameters, to develop a more comprehensive understanding of how the kidney environment affects antimicrobial activity. This knowledge will be vital in optimizing treatment strategies for pyelonephritis, ultimately improving patient outcomes.
Keywords: ddc:610